2019
DOI: 10.1097/md.0000000000017952
|View full text |Cite
|
Sign up to set email alerts
|

Antegrade intramedullary nail versus plate fixation in the treatment of humeral shaft fractures

Abstract: Protocols of systematic reviews and meta-analyses allow for planning and documentation of review methods, act as a guard against arbitrary decision making during review conduct, enable readers to assess for the presence of selective reporting against completed reviews, and, when made publicly available, reduce duplication of efforts and potentially prompt collaboration. Evidence documenting the existence of selective reporting and excessive duplication of reviews on the same or similar topics is accumulating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 82 publications
3
19
0
5
Order By: Relevance
“…Hongjie Wen et al in 2019 performed a meta-analysis to compare the efficacy and safety between antegrade IMN and plating for humeral shaft fracture, concluding that IMN may be superior to open reduction and internal fixation (ORIF) in reducing blood loss and post-operative infections, but inferior to minimally invasive plate osteosynthesis (MIPO) in nonunion rate. In the same study they found no statistically significant differences in operation time, functional results (evaluated with American Shoulder and Elbow Surgeons (ASES) score), rate of nerve injury, delayed union and need for reoperation 27 ( Figs. 5A, B; Figs.…”
Section: Intramedullary Nailingmentioning
confidence: 83%
See 1 more Smart Citation
“…Hongjie Wen et al in 2019 performed a meta-analysis to compare the efficacy and safety between antegrade IMN and plating for humeral shaft fracture, concluding that IMN may be superior to open reduction and internal fixation (ORIF) in reducing blood loss and post-operative infections, but inferior to minimally invasive plate osteosynthesis (MIPO) in nonunion rate. In the same study they found no statistically significant differences in operation time, functional results (evaluated with American Shoulder and Elbow Surgeons (ASES) score), rate of nerve injury, delayed union and need for reoperation 27 ( Figs. 5A, B; Figs.…”
Section: Intramedullary Nailingmentioning
confidence: 83%
“…Although several studies have compared the clinical outcomes of plating versus intramedullary nailing (IMN) in the treatment of humeral shaft fractures, the optimal surgical treatment remains controversial [26][27][28] . Hongjie Wen et al in 2019 performed a meta-analysis to compare the efficacy and safety between antegrade IMN and plating for humeral shaft fracture, concluding that IMN may be superior to open reduction and internal fixation (ORIF) in reducing blood loss and post-operative infections, but inferior to minimally invasive plate osteosynthesis (MIPO) in nonunion rate.…”
Section: Intramedullary Nailingmentioning
confidence: 99%
“…A meta-analysis was performed by Heinemann et al in 2010, where they did not find any noteworthy statistical difference between implants and in the rate of total complications,nerve-palsy non-union, ,infections or the need for reoperation. 16 For patients with humeral shaft fractures surgical treatment is usually indicated there is a neurovascular injury, open fractures, or where there is an associated elbow and forearm fractures, and polytrauma. Currently on the surgical protocol of humeral shaft fracture there is no clear agreement and guidance.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study was done by Davies et al where it was suggested that humeral MIPO results in remarkably lower pooled major complication rate than that of IMN. 16…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis have shown advantages of MIPO plates over endomedullary nails in nonunion rates and over open reduction and internal fixation in iatrogenic neurologic injury rates. 15 , 16 Compared with plate open reduction and internal fixation and endomedullary nails, the MIPO plate technique has also shown better clinical outcomes with a lower rate of complications. 6 Proximal metadiaphyseal fractures require long proximal humerus locking plates for stabilization making MIPO technique especially challenging in this area.…”
mentioning
confidence: 99%